TEXTBOOKS AS EDUCATIONAL TOOLS FOR TEACHING A SPORT CLASSIFICATION MODEL IN SCHOOL PHYSICAL EDUCATION - Ruggiero Barroso, Andre Luis; Darido, Suraya Cristina [UNESP] (Univ Fed Rio Grande Do Sul, Escola Educ Fisica, 2016)
This study investigated the changes carried out by Physical Education teachers regarding materials used to teach the sport classification system in the eight and nine years of Middle School, according to their needs, and if those changes are appropriate for another group of teachers who work at the same educational level. Action research was used and three categories were built: comprehension and evaluation of the sport classification system; comprehension and evaluation of teaching materials; and implementation of educational materials related to the sports classification system. In the first category, positive factors were higher than potential difficulties; in the second category, teachers were favorable to using of textbooks; and the third category examined the importance of the materials being always open to changes.
Keywords: Primary education; Sports; Classification; Teaching material